Fiber and fiber product
By using polyester pellets made from ethylene glycol derived from carbon monoxide or carbon dioxide, the challenge of producing environmentally friendly fibers and textile products is addressed, achieving reduced environmental impact and appropriate mechanical properties.
Patent Information
- Application Number
- JP2024111165
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-25
- Filing Date
- 2024-07-10
- Publication Date
- 2025-04-07
AI Technical Summary
There is a lack of clarity on whether fibers and textile products can be produced from polyesters made using ethanol derived from carbon monoxide gas or ethylene glycol derived from carbon dioxide gas as raw materials.
The development of polyester pellets using ethylene glycol made from carbon monoxide or carbon dioxide, which are then processed into fibers and textile products with specific intrinsic viscosity and thermal properties.
This approach enables the production of fibers and textile products that reduce environmental impact while maintaining suitable mechanical properties.
Smart Images

Figure 2025054180000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to textiles and textile articles. [Background technology]
[0002] Polyesters are widely used in various industrial applications because they are inexpensive and have excellent mechanical properties, chemical stability, heat resistance, transparency, etc. Polyesters are obtained by polycondensation of diol units and dicarboxylic acid units. For example, polyethylene terephthalate is produced by esterifying ethylene glycol and terephthalic acid as raw materials and then polycondensing them. These raw materials are produced from petroleum, which is a fossil resource. For example, ethylene glycol is industrially produced from ethylene, and terephthalic acid is industrially produced from xylene.
[0003] In recent years, with the growing demand for the creation of a recycling-oriented society, there is a desire to move away from fossil fuels in the materials field, just as there is in energy, and the production of polyester from raw materials other than fossil fuels, such as biomass, is being considered. Biomass is a non-exhaustible resource, an industrial resource originating from the constituent substances of living organisms. The carbon contained in biomass is derived from carbon dioxide absorbed from the atmosphere by photosynthesis during the growth of organisms, so even if carbon dioxide is emitted by burning biomass, it is thought that the amount of carbon dioxide in the atmosphere is not increased overall. For this reason, biomass is attracting attention as a carbon-neutral renewable energy source. Recently, the practical application of biomass plastics made from these biomass raw materials has progressed rapidly, and attempts have been made to produce polyester, a general-purpose polymer material, from these biomass raw materials (for example, Patent Documents 1 and 2). By using polyester produced from biomass-derived raw materials (biomass polyester) instead of polyester produced using raw materials derived from fossil fuels, it becomes possible to reduce the amount of fossil fuel used and the environmental burden.
[0004] Bioethanol, which is used to produce biomass polyester, is generally produced by sugar fermentation from edible raw materials such as sugarcane. However, it is known from experience that the yield of crops such as sugarcane is greatly affected by meteorological factors. Therefore, there are concerns that climate change will make it difficult to stably procure sugarcane, the raw material for bioethanol. Ethanol, which is also used as a raw material for plastics, has been produced from resources that are neither fossil fuels nor biomass. For example, ethanol has been produced by microbial fermentation using carbon monoxide present in exhaust gases generated from steelworks and factories as a raw material (e.g., Patent Document 3). Ethylene glycol has also been produced by electrolyzing carbon dioxide present in exhaust gases generated from steelworks and factories (e.g., Patent Document 4). Furthermore, production of polyesters from these compounds has also been considered. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2011-527348 [Patent Document 2] Special Publication No. 2012-519748 [Patent Document 3] Special Publication No. 2011-512869 [Patent Document 4] JP 2018-123390 A Summary of the Invention [Problem to be solved by the invention]
[0006] It has been known for some time that fibers and textile products can be produced from polyesters produced from petroleum-derived raw materials or biomass-derived raw materials. However, it was not clear whether fibers and textile products could be produced from polyesters produced using ethanol produced from carbon monoxide gas or ethylene glycol produced from carbon dioxide gas.
[0007] Therefore, an object of the present disclosure is to provide a fiber that can reduce the environmental impact. Another object of the present disclosure is to provide a textile product using the fiber. [Means for solving the problem]
[0008] The present inventors have found that polyester pellets produced using ethylene glycol produced from carbon monoxide gas or carbon dioxide gas as a raw material have a predetermined intrinsic viscosity and are suitable for processing into fibers and fiber products. The present disclosure was completed based on this knowledge and through further investigation.
[0009] The present disclosure is solved by the following embodiments. <1> A fiber using polyester pellets, the polyester pellets contain a polyester composed of diol units and dicarboxylic acid units, The diol unit contains ethylene glycol produced from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide, The intrinsic viscosity of the polyester pellets is 0.50 dL / g or more and 0.90 dL / g or less. <2> The dicarboxylic acid unit includes at least one selected from the group consisting of terephthalic acid derived from a fossil fuel, terephthalic acid derived from biomass, and terephthalic acid derived from carbon dioxide gas. <1> 2. The polyester pellet according to claim 1 . <3> The heat of fusion of the polyester pellets during the second heating step, as measured by differential scanning calorimetry (DSC) in accordance with JIS K7122:2012, is 8 J / g or more. <1> or <2> The fiber described in <4> The heat of solidification of the polyester pellets during the second cooling step, as measured by differential scanning calorimetry (DSC) in accordance with JIS K7122:2012, is 7 J / g or more. <1> ~ <3> 13. The fiber according to claim 12, <5> The Kjeldahl nitrogen content in the polyester pellets is 90 μg / g or less. <1> ~ <4> 13. The fiber according to claim 12, <6> The content of hydrogen molecules in the polyester pellets is 7.5×10 17 pcs / g or less, <1> ~ <5> 13. The fiber according to claim 12, <7> <1> ~ <6> A textile product using the fiber described in any one of the above. Effect of the Invention
[0010] The present disclosure can provide a fiber that can reduce the environmental impact. The present disclosure also provides textile products using the fibers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [polyester] The polyester constituting the polyester pellet according to the present disclosure is composed of diol units and dicarboxylic acid units, and is obtained by a polycondensation reaction using ethylene glycol as the diol units and dicarboxylic acid as the dicarboxylic acid units, which are derived from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide.
[0012] Ethylene glycol using carbon monoxide gas as a raw material can be produced from ethanol produced using carbon monoxide gas as a raw material. For example, ethylene glycol using carbon monoxide gas as a raw material can be obtained by, for example, producing ethylene glycol from ethanol produced using carbon monoxide gas as a raw material by a conventionally known method via ethylene oxide.
[0013] <Microbial fermentation> Ethanol, which is made from carbon monoxide gas, can be obtained by microbial fermentation.
[0014] Microbial fermentation is carried out, for example, in a fermenter filled with a culture solution containing water and microorganisms. A raw material gas containing carbon monoxide gas is supplied into the fermenter, and the carbon monoxide gas is converted into ethanol inside the fermenter. The raw material gas may contain carbon dioxide, nitrogen, oxygen, etc. in addition to carbon monoxide.
[0015] The fermenter is preferably a continuous fermentation apparatus, and may be any of agitation type, airlift type, bubble column type, loop type, open bond type, and photobio type. The raw material gas and the culture solution may be continuously supplied to the fermenter, but it is not necessary to supply the raw material gas and the culture solution simultaneously, and the raw material gas may be supplied to the fermenter to which the culture solution has been previously supplied. The raw material gas is generally blown into the fermenter through a sparger or the like.
[0016] The culture medium is not particularly limited as long as it has an appropriate composition for culturing microorganisms, but is a liquid containing water as the main component and nutrients (e.g., vitamins, phosphoric acid, etc.) dissolved or dispersed in the water.
[0017] The temperature of the fermenter is preferably controlled to 40° C. or lower. By controlling the temperature to 40° C. or lower, the microorganisms in the fermenter do not die, and ethanol is efficiently produced by contacting the raw material gas with the microorganisms. The temperature of the fermenter is more preferably 38° C. or lower, and in order to enhance the activity of the microorganisms, is preferably 10° C. or higher, more preferably 20° C. or higher, and even more preferably 30° C. or higher.
[0018] The microorganism (species) that ferments the raw gas is not particularly limited as long as it can produce ethanol by microbial fermentation of the raw gas using carbon monoxide as the main raw material. For example, the microorganism (species) is preferably one that produces ethanol from the raw gas by the fermentation action of gas-utilizing bacteria. Among gas-utilizing bacteria, the genus Clostridium is preferred from the viewpoint of gas utilization and culture stability, and Clostridium autoethanogenum is more preferred. Examples are given in more detail below.
[0019] Gas-utilizing bacteria include both Eubacteria and Archaea. Examples of eubacteria include bacteria of the genus Clostridium, Moorella, Acetobacterium, Carboxydocella, Rhodopseudomonas, Eubacterium, Butyribacterium, Oligotropha, Bradyrhizobium, and the aerobic hydrogen-oxidizing bacteria Ralsotonia.
[0020] On the other hand, examples of archaea include bacteria of the genus Methanobacterium, bacteria of the genus Methanobrevibacter, bacteria of the genus Methanocalculus, bacteria of the genus Methanococcus, bacteria of the genus Methanosarcina, bacteria of the genus Methanosphaera, bacteria of the genus Methanothermobacter, Metha Examples include bacteria of the genus Nothrix, bacteria of the genus Methanoculleus, bacteria of the genus Methanofollis, bacteria of the genus Methanogenium, bacteria of the genus Methanospirillium, bacteria of the genus Methanosaeta, bacteria of the genus Thermococcus, bacteria of the genus Thermofilum, bacteria of the genus Arcaheoglobus, and the like. Among these, as archaea, bacteria of the genus Methanosarcina, bacteria of the genus Methanococcus, bacteria of the genus Methanothermobacter, bacteria of the genus Methanothrix, bacteria of the genus Thermococcus, bacteria of the genus Thermofilum, and bacteria of the genus Archaeoglobus are preferred.
[0021] Furthermore, because of their excellent carbon monoxide and carbon dioxide assimilation ability, archaea are preferably Methanosarcina bacteria, Methanothermobactor bacteria, or Methanococcus bacteria, and more preferably Methanosarcina bacteria or Methanococcus bacteria. Specific examples of Methanosarcina bacteria include Methanosarcina barkeri, Methanosarcina mazei, and Methanosarcina acetivorans.
[0022] Among the gas-utilizing bacteria described above, it is preferable to select and use bacteria with high ethanol production ability, such as Clostridium autoethanogenum, Clostridium ljungdahlii, Clostridium aceticum, Clostridium carboxidivorans, Moorella thermoacetica, and Acetobacterium woodii.
[0023] Ethanol produced by microbial fermentation is obtained, for example, as an ethanol-containing liquid mixed with a culture liquid. Ethanol can be separated from this ethanol-containing liquid using a separation device. Examples of separation devices include solid-liquid separation devices, distillation devices, and separation membranes, and it is preferable to use a combination of a solid-liquid separation device and a distillation device. The separation process performed by combining a solid-liquid separation device and a distillation device will be specifically described below.
[0024] The ethanol-containing liquid obtained by microbial fermentation is separated into a solid component mainly composed of microorganisms and a liquid component containing ethanol in a solid-liquid separation device. The ethanol-containing liquid obtained by microbial fermentation contains, in addition to the target ethanol, microorganisms contained in the fermenter and their dead bodies as solid components, so solid-liquid separation is performed to remove these. Examples of solid-liquid separation devices include filters, centrifuges, and devices that use a solution precipitation method. The solid-liquid separation device may also be a device (e.g., a heat drying device) that evaporates the liquid component containing ethanol from the ethanol-containing liquid and separates it from the solid component. At this time, all of the liquid component containing the target ethanol may be evaporated, or the liquid component may be partially evaporated so that the target ethanol is preferentially evaporated.
[0025] The liquid component separated by solid-liquid separation is further distilled in a distillation apparatus to separate the target ethanol. Separation by distillation makes it possible to purify ethanol in large quantities to a high purity with a simple operation. When distillation is performed, a known distillation apparatus such as a distillation column may be used. In addition, the distillation is performed, for example, so that the distillate contains the target ethanol at a high purity, while the bottoms (i.e., distillation residue) contains water as a main component (for example, 70 mass% or more, preferably 90 mass% or more). By performing the operation in this manner, the target ethanol and water can be largely separated.
[0026] The temperature inside the distillation apparatus during the distillation of ethanol is not particularly limited, but is preferably 100° C. or lower, more preferably 95° C. or lower, and is preferably 70° C. or higher. By setting the temperature inside the distillation apparatus within the above range, it is possible to reliably separate ethanol from other components such as water. The pressure (gauge pressure) in the distillation apparatus during the distillation of ethanol may be normal pressure, but is preferably lower than atmospheric pressure, more preferably 150 kPa or less, and also preferably 60 kPa or more. By setting the pressure in the distillation apparatus within the above range, the separation efficiency of ethanol can be improved, and the yield of ethanol can be improved.
[0027] <Electrolysis> Ethylene glycol can be produced from carbon dioxide gas by electrolysis. A method for producing ethylene glycol from carbon dioxide gas by electrolysis will be described below.
[0028] Electrolysis can be carried out, for example, using an electrolysis cell that includes an anode, a cathode, and an ion exchange membrane disposed to separate the anode and the cathode.
[0029] The anode oxidizes water (HO) to produce oxygen (O) and hydrogen ions (H +) is generated. Alternatively, hydroxide ions (OH - ) to generate oxygen (O2) and water (H2O). On the other hand, the cathode is charged with hydrogen ions (H + ) and electrons (e - ) to reduce carbon dioxide (CO2) and to produce carbon compounds such as ethylene glycol (C2H6O2). In this way, by reducing carbon dioxide on the cathode side of the electrolysis cell, it is possible to produce ethylene glycol using carbon dioxide as a raw material.
[0030] The anode is preferably mainly composed of a catalytic material capable of reducing the overvoltage of the reaction of oxidizing water or hydroxide ions. Examples of such catalytic materials include metals such as platinum (Pt), palladium (Pd), and nickel (Ni), alloys and intermetallic compounds containing these metals, binary metal oxides such as manganese oxide (Mn-O), iridium oxide (Ir-O), nickel oxide (Ni-O), cobalt oxide (Co-O), iron oxide (Fe-O), tin oxide (Sn-O), indium oxide (In-O), ruthenium oxide (Ru-O), lithium oxide (Li-O), and lanthanum oxide (La-O), ternary metal oxides such as Ni-Co-O, Ni-Fe-O, La-Co-O, Ni-La-O, and Sr-Fe-O, quaternary metal oxides such as Pb-Ru-Ir-O and La-Sr-Co-O, and metal complexes such as Ru complexes and Fe complexes.
[0031] The cathode is preferably made of a catalytic material capable of reducing the overvoltage of the reaction of reducing carbon dioxide. Examples of such catalytic materials include metals such as gold (Au), silver (Ag), copper (Cu), platinum (Pt), palladium (Pd), nickel (Ni), cobalt (Co), iron (Fe), manganese (Mn), titanium (Ti), cadmium (Cd), zinc (Zn), indium (In), gallium (Ga), lead (Pb), and tin (Sn), metal materials such as alloys and intermetallic compounds containing at least one of these metals, carbon materials such as carbon (C), graphene, CNT (carbon nanotube), fullerene, and Ketjen Black, and metal complexes such as Ru complexes and Re complexes.
[0032] <Diol unit> The diol unit used in the present disclosure may not be only ethylene glycol made from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide. That is, ethylene glycol made from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide may be used in combination with other diols. Even if it is used in combination with other diols, the present disclosure aims to reduce the environmental load by using ethylene glycol made from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide.
[0033] Other diols include diols derived from fossil fuels and diols derived from biomass.
[0034] As the diol derived from fossil fuel, a compound having two or more, preferably two to eight hydroxyl groups in one molecule can be used. Specifically, as the diol derived from fossil fuel, there is no particular limitation and a conventionally known substance can be used, for example, polypropylene glycol (PPG), neopentyl glycol (NPG), ethylene glycol (EG), diethylene glycol (DEG), butylene glycol (BG), hexamethylene glycol, triethylene glycol, dipropylene glycol, 1,4-cyclohexanedimethanol, 1,9-nonanediol, 3-methyl-1,5-pentanediol, etc. can be used. These may be used alone or in combination of two or more.
[0035] As the biomass-derived diol, an aliphatic diol obtained from a plant raw material such as corn, sugarcane, cassava, or sago palm can be used. As the biomass-derived aliphatic diol, for example, polypropylene glycol (PPG), neopentyl glycol (NPG), ethylene glycol (EG), diethylene glycol (DEG), butylene glycol (BG), hexamethylene glycol, etc., which are obtained from a plant raw material by the following method, can be used, and any of them can be used. These may be used alone or in combination.
[0036] Biomass-derived polypropylene glycol is produced by a fermentation method in which glucose is obtained by decomposing plant raw materials, via 3-hydroxypropylaldehyde (HPA) from glycerol. Compared with polypropylene glycol produced by the EO production method, polypropylene glycol produced by a biomethod such as the fermentation method is preferable in terms of safety, since useful by-products such as lactic acid can be obtained, and the production cost can be kept low. Biomass-derived butylene glycol can be produced from biomass-derived succinic acid. Specifically, glycol is produced from a plant raw material, and the glycol is fermented to obtain biomass-derived succinic acid. Biomass-derived butylene glycol can be produced by adding water to biomass-derived succinic acid. Biomass-derived ethylene glycol can be produced, for example, from bioethanol obtained by a conventional method via ethylene.
[0037] <Dicarboxylic acid unit> The dicarboxylic acid unit of the polyester is, for example, a dicarboxylic acid derived from a fossil fuel. As the dicarboxylic acid derived from a fossil fuel, aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and derivatives thereof can be used without limitation. Examples of aromatic dicarboxylic acids include terephthalic acid and isophthalic acid, and examples of derivatives of aromatic dicarboxylic acids include lower alkyl esters of aromatic dicarboxylic acids, specifically, methyl esters, ethyl esters, propyl esters, butyl esters, etc. Among these, terephthalic acid is preferred, and dimethyl terephthalate is preferred as a derivative of aromatic dicarboxylic acid. In addition, specific examples of the aliphatic dicarboxylic acid include linear or alicyclic dicarboxylic acids having 2 to 40 carbon atoms, such as oxalic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, dimer acid, and cyclohexanedicarboxylic acid. In addition, examples of the derivatives of the aliphatic dicarboxylic acids include lower alkyl esters such as methyl esters, ethyl esters, propyl esters, and butyl esters of the above aliphatic dicarboxylic acids, and cyclic acid anhydrides of the above aliphatic dicarboxylic acids, such as succinic anhydride. Among these, adipic acid, succinic acid, dimer acid, or a mixture thereof is preferred, and those mainly composed of succinic acid are particularly preferred. Examples of the derivatives of the aliphatic dicarboxylic acid include methyl esters of adipic acid and succinic acid, or a mixture thereof.
[0038] The dicarboxylic acid used in the dicarboxylic acid unit may be a biomass-derived dicarboxylic acid. As the biomass-derived dicarboxylic acid, aliphatic dicarboxylic acids obtained from plant raw materials such as renewable plant-derived oils such as soybean oil, linseed oil, tung oil, coconut oil, palm oil, castor oil, etc., and regenerated oils obtained by recycling waste edible oils mainly containing these oils can be used. Examples of biomass-derived aliphatic dicarboxylic acids include sebacic acid, succinic acid, phthalic acid, adipic acid, glutaric acid, dimer acid, etc. For example, sebacic acid is produced by alkaline pyrolysis of ricinoleic acid obtained from castor oil, with heptyl alcohol as a by-product. As the aromatic dicarboxylic acid derived from biomass, terephthalic acid derived from biomass can be used. The terephthalic acid derived from biomass can be produced, for example, by producing isobutanol from corn, sugars, or wood, converting the isobutanol into isobutylene, dimerizing the isobutane to produce isooctene, synthesizing p-xylene through radical cleavage, recombination, and cyclization, and then oxidizing the xylene (International Publication No. WO 2009 / 079213). When a biomass-derived dicarboxylic acid is used as the dicarboxylic acid unit, in the present disclosure, it is particularly preferable to use biomass-derived terephthalic acid.
[0039] The dicarboxylic acid unit of the polyester may be a dicarboxylic acid produced from carbon dioxide gas as a raw material. An example of a dicarboxylic acid made from carbon dioxide gas is terephthalic acid made from carbon dioxide gas. Terephthalic acid made from carbon dioxide gas can be produced by, for example, using a composite catalyst containing chromium oxide and a specific H-ZSM-5 zeolite to produce p-xylene from carbon dioxide gas and hydrogen gas as raw materials, and then oxidizing the p-xylene (JP Patent Publication No. 2019-205969).
[0040] These dicarboxylic acids may be used alone or in combination of two or more.
[0041] The polyester contained in the polyester pellet according to the present disclosure may be a copolymer polyester in which a copolymer component is added as a third component in addition to the above diol unit and dicarboxylic acid unit. Specific examples of the copolymer component include bifunctional oxycarboxylic acid, and at least one polyfunctional compound selected from the group consisting of trifunctional or more polyhydric alcohols, trifunctional or more polycarboxylic acids and / or their anhydrides, and trifunctional or more oxycarboxylic acids to form a crosslinked structure. Among these copolymer components, bifunctional and / or trifunctional or more oxycarboxylic acids are particularly preferably used because they can easily produce a copolymer polyester with a high degree of polymerization. Among them, the use of trifunctional or more oxycarboxylic acids is most preferred because they can easily produce a polyester with a high degree of polymerization with a very small amount without using a chain extender described later.
[0042] The polyester may be a high molecular weight polyester obtained by chain-extending (coupling) these copolymer polyesters. As the chain extender, a carbonate compound, a diisocyanate compound or the like may be used, and the amount of the carbonate bond and the urethane bond is usually 10 mol % or less, preferably 5 mol % or less, more preferably 3 mol % or less, based on 100 mol % of all monomer units constituting the polyester.
[0043] Specific examples of carbonate compounds include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, m-cresyl carbonate, dinaphthyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, ethylene carbonate, diamyl carbonate, dicyclohexyl carbonate, etc. In addition, carbonate compounds composed of the same or different hydroxy compounds derived from hydroxy compounds such as phenols and alcohols can be used.
[0044] Specific examples of the diisocyanate compound include known diisocyanates such as 2,4-tolylene diisocyanate, a mixture of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, diphenylmethane diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.
[0045] The polyester contained in the polyester pellet according to the present disclosure can be obtained by a conventionally known method of polycondensing the above-mentioned diol unit and dicarboxylic acid unit. Specifically, the polyester can be produced by a general melt polymerization method in which the above-mentioned diol unit and dicarboxylic acid unit are subjected to an esterification reaction and / or an ester exchange reaction, followed by a polycondensation reaction under reduced pressure, or by a known solution heating dehydration condensation method using an organic solvent.
[0046] The amount of diol used in producing the polyester is substantially equimolar to 100 moles of the dicarboxylic acid or its derivative. Generally, however, the diol is used in an excess of 0.1 mol % or more and 20 mol % or less, since distillates are generated during the esterification and / or transesterification reaction and / or condensation polymerization reaction.
[0047] The polycondensation reaction is preferably carried out in the presence of a polymerization catalyst. The timing of adding the polymerization catalyst is not particularly limited as long as it is before the polycondensation reaction, and the catalyst may be added when the raw materials are charged or when the pressure reduction is started.
[0048] The polymerization catalyst generally includes compounds containing metal elements of Groups 1 to 14 of the periodic table, excluding hydrogen and carbon. Specifically, compounds containing organic groups such as carboxylates, alkoxy salts, organic sulfonates, or β-diketonate salts containing at least one metal selected from the group consisting of titanium, zirconium, tin, antimony, cerium, germanium, zinc, cobalt, manganese, iron, aluminum, magnesium, calcium, strontium, sodium, and potassium, and further inorganic compounds such as oxides and halides of the above metals and mixtures thereof. Among these, metal compounds containing titanium, zirconium, germanium, zinc, aluminum, magnesium, and calcium, and mixtures thereof are preferred, and titanium compounds, zirconium compounds, and germanium compounds are particularly preferred. In addition, the catalyst is preferably a compound that is liquid during polymerization or dissolves in an ester oligomer or polyester, because the polymerization rate increases when the catalyst is in a molten or dissolved state during polymerization.
[0049] As the titanium compound, tetraalkyl titanate is preferred, specifically, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-t-butyl titanate, tetraphenyl titanate, tetracyclohexyl titanate, tetrabenzyl titanate, and mixed titanates thereof can be mentioned. In addition, titanium (oxy) acetylacetonate, titanium tetraacetylacetonate, titanium (diisopropoxide) acetylacetonate, titanium bis (ammonium lactate) dihydroxide, titanium bis (ethylacetoacetate) diisopropoxide, titanium (triethanolamine) isopropoxide, polyhydroxytitanium stearate, titanium lactate, titanium triethanolamine, butyl titanate dimer, etc. can also be preferably used. Furthermore, titanium oxide and composite oxides containing titanium and silicon can also be preferably used. Among these, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, titanium bis(ammonium lactate) dihydroxide, polyhydroxytitanium stearate, titanium lactate, butyl titanate dimer, titanium oxide, and titania / silica composite oxide (e.g., product name: C-94 manufactured by Acordis Industrial Fibers) are preferred, and tetra-n-butyl titanate, polyhydroxytitanium stearate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, and titania / silica composite oxide (e.g., product name: C-94 manufactured by Acordis Industrial Fibers) are particularly preferred.
[0050] Specific examples of the zirconium compound include zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, zirconyl diacetate, zirconium oxalate, zirconyl oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium ethoxide, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, zirconium tetra-t-butoxide, zirconium tributoxyacetylacetonate, and mixtures thereof. Zirconium oxide and composite oxides containing, for example, zirconium and silicon may also be used. Among these, zirconyl diacetate, zirconium tris(butoxy)stearate, zirconium tetraacetate, zirconium acetate hydroxide, ammonium zirconium oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, and zirconium tetra-t-butoxide are preferred.
[0051] Specific examples of germanium compounds include inorganic germanium compounds such as germanium oxide and germanium chloride, and organic germanium compounds such as tetraalkoxygermanium. In view of cost and availability, germanium oxide, tetraethoxygermanium, tetrabutoxygermanium, and the like are preferred, with germanium oxide being particularly preferred.
[0052] When using metal compounds as these polymerization catalysts, the amount of catalyst used is usually 5 ppm or more, preferably 10 ppm or more, and the upper limit is usually 30,000 ppm or less, preferably 1000 ppm or less, more preferably 250 ppm or less, and particularly preferably 130 ppm or less, as the amount of metal relative to the polyester produced. If the amount of catalyst used is too large, not only is it economically disadvantageous, but the thermal stability of the polymer is also reduced. If the amount of catalyst used is too small, the polymerization activity is reduced, and decomposition of the polymer is easily induced during the polymer production. As for the amount of catalyst used here, the method of reducing the amount of catalyst used is a preferred embodiment, since the amount of terminal carboxyl groups of the polyester produced is reduced as the amount of catalyst used is reduced.
[0053] The reaction temperature of the esterification reaction and / or transesterification reaction between the diol unit and the dicarboxylic acid unit is usually in the range of 150° C. to 260° C., and the reaction atmosphere is usually an inert gas atmosphere such as nitrogen or argon. The reaction pressure is usually normal pressure to 10 kPa. The reaction time is usually 1 hour to 10 hours.
[0054] In the above-mentioned production process, a chain extender (coupling agent) may be added to the reaction system. After the polycondensation is completed, the chain extender is added to the reaction system in a homogeneous molten state without using a solvent, and reacted with the polyester obtained by the polycondensation.
[0055] High molecular weight polyesters using these chain extenders (coupling agents) can be produced using known techniques. After polycondensation is completed, the chain extender is added to the reaction system in a homogeneous molten state without using a solvent, and reacted with the polyester obtained by polycondensation. Specifically, a polyester prepolymer having a terminal group substantially containing a hydroxyl group and a mass average molecular weight (Mw) of 20,000 or more, preferably 40,000 or more, obtained by catalytic reaction of a diol with a dicarboxylic acid, is reacted with the chain extender to obtain a polyester with a higher molecular weight. If the prepolymer has a mass average molecular weight of 20,000 or more, a small amount of coupling agent is used, and even under harsh conditions such as a molten state, it is not affected by the remaining catalyst, so that a high molecular weight polyester can be produced without generating gel during the reaction.
[0056] [Polyester pellets] The polyester pellets according to the present disclosure can be obtained by molding the polyester obtained as described above by a known method. For example, the polyester is extracted in the form of a strand from a polymerization reaction tank, and pelletized using a fixed or rotary cutter or pelletizer while or after cooling with water or air. The shape of the pellets after molding can be cylindrical with a circular or elliptical cross section, or spherical.
[0057] After the polyester is pelletized, solid-phase polymerization may be carried out as necessary to further increase the degree of polymerization or to remove oligomers such as cyclic trimers. Specifically, the polyester is pelletized and dried, and then pre-crystallized by heating at a temperature of 100° C. to 180° C. for 1 hour to 8 hours, and then heated at a temperature of 190° C. to 230° C. under an inert gas flow or under reduced pressure for 1 hour to several tens of hours.
[0058] The diameter of the polyester pellets is adjusted by adjusting the diameter of the outlet from the polymerization reactor, the strand withdrawal speed, the take-up speed, the cutting speed, etc. Specifically, the diameter is adjusted by adjusting the pressure in the polymerization reactor when the polymer is withdrawn or by adjusting the cutting speed of the rotary strand cutter.
[0059] The diameter of the obtained polyester pellets is usually 0.1 mm or more, preferably 0.2 mm or more, more preferably 0.5 mm or more, and most preferably 1 mm or more, and the upper limit (maximum diameter) is 20 mm or less, preferably 10 mm or less, more preferably 7 mm or less, and most preferably 4 mm or less. If the diameter is too small, degradation due to hydrolysis during pellet storage tends to become significant, and if the diameter is too large, the pellets tend to be poorly inserted during molding, resulting in unevenness in the product. The diameter of the polyester pellet referred to here means the diameter or length of the cross section of the polyester pellet, and the cross section of the polyester pellet means the cross section having the maximum cross-sectional area of the polyester pellet.
[0060] In the polyester pellets according to the present disclosure, the proportion of powders having a maximum diameter of less than 1 mm is preferably 2.0% by weight or less, and more preferably 1.0% by weight or less. If the proportion of powders having a maximum diameter of less than 1 mm is high, the powders will be poorly inserted into the molding machine screw during melt molding, resulting in a long residence time in the molding machine, and will be prone to thermal degradation due to their large surface area, which will be mixed into the molded product as foreign matter such as burns and bumps, leading to problems such as a decrease in the mechanical strength of the molded product and poor appearance.
[0061] The intrinsic viscosity of the polyester pellets according to the present disclosure is 0.50 dL / g or more and 0.90 dL / g or less, preferably 0.60 dL / g or more and 0.85 dL / g or less, more preferably 0.65 dL / g or more and 0.80 dL / g or less. If the intrinsic viscosity is less than 0.50 dL / g, the mechanical properties required for the fiber or fiber product manufactured using the polyester pellets may be insufficient. On the other hand, if the intrinsic viscosity is more than 0.90 dL / g, the productivity is impaired in the manufacturing process of the raw material, the manufacturing process of the fiber, and the manufacturing process of the fiber product. The intrinsic viscosity of the polyester pellets according to the present disclosure is a value calculated from the melt viscosity measured at 35° C. using a phenol / tetrachloroethane solvent (component ratio: 3 / 2).
[0062] Polyester pellets having a desired intrinsic viscosity can be obtained by adjusting the polycondensation reaction temperature, polycondensation reaction pressure, polycondensation reaction time, solid-phase polymerization temperature, solid-phase polymerization pressure, solid-phase polymerization time, and the like. The higher the temperature of the polycondensation reaction, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the lower the temperature of the polycondensation reaction, the lower the intrinsic viscosity of the resulting polyester pellets tends to be. The higher the pressure of the polycondensation reaction, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the lower the pressure of the polycondensation reaction, the lower the intrinsic viscosity of the resulting polyester pellets tends to be. The longer the polycondensation reaction time, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the shorter the polycondensation reaction time, the lower the intrinsic viscosity of the resulting polyester pellets tends to be. The higher the temperature of the solid-phase polymerization, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the lower the temperature of the solid-phase polymerization, the lower the intrinsic viscosity of the resulting polyester pellets tends to be. The higher the pressure of the solid-state polymerization, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the lower the pressure of the solid-state polymerization, the lower the intrinsic viscosity of the resulting polyester pellets tends to be. The longer the solid-state polymerization time, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the shorter the solid-state polymerization time, the lower the intrinsic viscosity of the resulting polyester pellets tends to be.
[0063] In the polyester pellets according to the present disclosure, the heat of fusion during the second heating and the heat of solidification during the second cooling, which are obtained by differential scanning calorimetry (DSC) in accordance with JIS K7122:2012 (measurement method for heat of transition of plastics), tend to be larger than those of conventional polyester pellets derived from fossil fuels. For example, the heat of fusion of the polyester pellets according to the present disclosure at the second heating step obtained by DSC according to JIS K7122:2012 is preferably 8 J / g or more, more preferably 11 J / g or more, and even more preferably 13 J / g or more. Also, the heat of fusion of the polyester pellets according to the present disclosure at the second heating step obtained by DSC according to JIS K7122:2012 is preferably 25 J / g or less, more preferably 20 J / g or less, and even more preferably 15 J / g or less. For example, the heat of solidification of the polyester pellets according to the present disclosure at the second cooling step, as measured by DSC in accordance with JIS K7122:2012, is preferably 7 J / g or more, more preferably 9 J / g or more, and even more preferably 12 J / g or more. Also, the heat of solidification of the polyester pellets according to the present disclosure at the second cooling step, as measured by DSC in accordance with JIS K7122:2012, is preferably 25 J / g or less, more preferably 20 J / g or less, and even more preferably 15 J / g or less. The specific method for measuring DSC is to use a differential scanning calorimeter and to perform the measurement according to the method described in the Examples below.
[0064] In the polyester pellets according to the present disclosure, the Kjeldahl nitrogen content tends to be smaller than that of conventional polyester pellets derived from fossil fuels. For example, the Kjeldahl nitrogen content in the polyester pellets according to the present disclosure is preferably 90 μg / g or less, more preferably 80 μg / g or less, and even more preferably 75 μg / g or less. In addition, the Kjeldahl nitrogen content in the polyester pellets according to the present disclosure is 0 μg / g or more, practically 10 μg / g or more, and more practically 30 μg / g or more. In the present disclosure, Kjeldahl nitrogen is nitrogen quantified in accordance with JIS K0102:2019 44.1 (Kjeldahl method) and 44.2 (Indophenol blue absorptiometry). The specific method for measuring the content of Kjeldahl nitrogen is measured by the method described in the Examples below.
[0065] In the polyester pellets according to the present disclosure, the hydrogen molecule content tends to be smaller than that of conventional polyester pellets derived from fossil fuels. For example, the hydrogen molecule content in the polyester pellets according to the present disclosure is 7.5×10 17 It is preferable that the number of particles is less than 7.0×10 17 More preferably, it is 6.6×10 17 The content of hydrogen molecules in the polyester pellets according to the present disclosure is preferably 0 or more and more preferably 1.0×10 17 It is practical to have a density of 3.0×10 17 It is more practical to have more than one piece / g. The content of hydrogen molecules in the polyester pellets is measured by thermal desorption spectrometry-mass spectrometry (TDS-MS), specifically, by the method described in the Examples below.
[0066] In the production process of polyester pellets or to the produced polyester pellets, various additives may be added within the range that does not impair the properties, such as plasticizers, UV stabilizers, coloring inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, thread friction reducing agents, release agents, antioxidants, ion exchange agents, color pigments, etc. These additives are added in the range of 5% by mass to 50% by mass based on the total amount of the polyester pellets.
[0067] The polyester pellets according to the present disclosure can be used to manufacture fibers or textile products, as described below. However, the uses of the polyester pellets according to the present disclosure are not limited thereto, and they can also be used, for example, to manufacture molded articles or films.
[0068] [fiber] The fibers according to the present disclosure are made using the polyester pellets described above. The fibers according to the present disclosure may be in any form, such as long fibers (filaments) or short fibers (staples). In the case of long fibers, they may be monofilaments consisting of one single yarn, or multifilaments consisting of multiple single yarns. In the case of short fibers, there are no limitations on the cut length or the number of crimps. The cross-sectional shape of the fibers according to the present disclosure can be not only round, but also a wide variety of cross-sectional shapes such as flat, Y-shaped, T-shaped, hollow, R-shaped, and Well-shaped.
[0069] The fineness of the fibers may be appropriately set depending on the application, and in the case of long fibers for clothing, it is practically preferable that the fineness is 8 dtex or more and 150 dtex or less. Furthermore, for clothing, a strength of 1.5 cN / dtex or more is preferable, but by taking measures such as combining it with other fibers when producing a fabric, a strength of 1.5 cN / dtex or less can be used without any problems. The elongation may be appropriately set depending on the application, and is preferably 25% to 60% in terms of processability when processed into a fabric. When post-processing is performed, it is preferable to set the elongation to 60% to 250%.
[0070] The polyester pellets can be processed into fibers by a conventional method for processing polyester pellets into fibers. Hereinafter, a melt spinning method, which is an example of a method for processing polyester pellets into fibers, will be described.
[0071] The raw material polyester pellets are melted, metered and transported by a gear pump, and discharged from a spinneret. The yarn is cooled to room temperature by blowing cooling air onto it using a yarn cooling device such as a chimney, oiled and focused in an oiling device, entangled in a fluid entangling nozzle device, passed through take-up rollers and stretching rollers, and stretched according to the ratio of the peripheral speeds of the take-up rollers and stretching rollers, and can be processed into fibers. Furthermore, the yarn may be heat-set by a stretching roller and wound up by a winder (winding device). Alternatively, the peripheral speed of the take-up roller and the drawing roller may be set to the same speed, and the yarn may be wound up by a winder operating at the same speed to produce an undrawn yarn, which may then be drawn in a separate process.
[0072] The fibers can be post-processed, such as by false twisting or twisting, and can be woven or knitted in the same way as ordinary fibers.
[0073] [Textile products] The fibers according to the present disclosure can be made into textile products according to known methods, including gauze, filters, carpets, automotive interior materials, clothing, woven fabrics, knitted fabrics, pile fabrics, nonwoven fabrics, spun yarns, wadding, and the like. Furthermore, the textile products according to the present disclosure may have any weave or knit structure, and preferably include plain weave, twill weave, satin weave, or variations thereof, warp knit, weft knit, circular knit, lace knit, or variations thereof. EXAMPLES
[0074] The present disclosure will be described more specifically below with reference to examples, but the present disclosure is not limited to the following examples.
[0075] <Preparation of polyester pellets> [Example 1] A medium for microbial fermentation was prepared containing the following components in 1 L of distilled water. (Medium composition) 0.5g MgCl2 6H2O 0.2g NaCl 100mM sodium phosphate buffer pH 6.0 160mL 0.6g NH4Cl 0.05mL 85% H3PO4 0.15g KCl ·Trace metal complex solution (LS06) 10mL Vitamin B Complex Solution (LS03) 10mL 1000mg / L Resazurin 1mL 0.0025g FeCl3 · Cysteine HCl monohydrate 0.75g 15g agarose 100 mM sodium phosphate buffer solution was prepared by dissolving 13.2 g of NaH2PO4 and 1.1 g of Na2HPO4·7H2O in 1 L of water.
[0076] In addition, a Clostridium autoethanogenum culture was prepared as a culture for microbial fermentation. The Clostridium autoethanogenum in the culture was obtained from the German Resource Centre for Biological Material (DSMZ), and the accession number given to the bacterium is DSMZ10061.
[0077] A 5 L continuous stirred tank reactor was charged with 4.9 L of the above medium. The headspace gas of the continuous stirred tank reactor was switched to 95% CO, 5% CO2 at atmospheric pressure. 100 mL of Clostridium autoethanogenum culture was inoculated. The continuous stirred tank reactor was maintained at 37 °C and stirred at 200 rpm at the beginning of the culture and 400 rpm during the growth phase. During stirring, the pH of the culture was maintained at 5.5 by automatic addition of 5 M NaOH.
[0078] A sterile serum bottle with a volume of 234 mL was purged three times with steel mill waste gas (composition: 53% CO, 18% CO2, 26% N2, 3% H2) and then evacuated to a vacuum of -5 psi. 50 mL of the above culture was directly transferred into the serum bottle. The head space of the serum bottle was filled with the above waste gas and pressurized to 25 psig while maintaining the reaction temperature at 37°C using a shaking incubator. The culture was incubated at 37°C with shaking. After 5 hours, the ethanol concentration of the culture was 1.675 g / L, confirming the production of ethanol by microbial fermentation.
[0079] The culture solution after microbial fermentation was separated into solid and liquid components using a solid-liquid separation filter device under conditions of a culture solution introduction pressure of 200 kPa or more. The liquid component was then introduced into a distillation apparatus equipped with a heater using steam at 170° C. The temperature of the bottom of the distillation column was raised to 101° C. within 15 minutes, and the liquid component was then introduced into the middle of the distillation column. During continuous operation, the column was operated continuously at 101° C. at the bottom, 99° C. at the middle, and 91° C. at the top at 15 sec / L to purify ethanol.
[0080] Purified ethanol was supplied to a multi-tube, externally heated, isothermal reactor packed with 1.5 L of γ-AlO catalyst (3 mmΦ×3 mmH) at a rate of 10 L / Hr and a pressure of 10 kg / cm 2 G. The reaction was carried out at 370°C for 500 hours, and ethylene was produced by the intramolecular dehydration reaction of ethanol.
[0081] The produced ethylene was introduced into an ethylene oxidation reactor and catalytically oxidized in gas phase with a molecular oxygen-containing gas in the presence of a silver catalyst to obtain a reaction product gas containing ethylene oxide. The reaction product gas containing ethylene oxide was supplied to the lower part of the ethylene oxide absorption tower, and water was introduced from the upper part of the ethylene oxide absorption tower and brought into countercurrent contact with the reaction product gas, so that the ethylene oxide in the reaction product gas was absorbed in the water. The unabsorbed gas near the top of the ethylene oxide absorption tower was circulated to the ethylene oxidation reaction apparatus. The bottom liquid of the ethylene oxide absorption tower was supplied to the upper part of the ethylene oxide stripper tower, the top pressure of which was 0.045 MPa (gauge) and the bottom temperature of which was 115°C. A part of the bottom liquid of the ethylene oxide absorption tower was circulated to the ethylene oxide absorption tower. The vapor stripped near the top of the ethylene oxide stripper was condensed in a condenser, a part of which was refluxed to the ethylene oxide stripper and a part of which was supplied to the ethylene oxide dehydration tower. The vapor near the top of the ethylene oxide dehydration tower was condensed in a condenser, a part of the condensate was refluxed to the dehydration tower, and the remainder of the condensate was supplied to the light fraction separation tower. The vapor near the top of the light fraction separation column was sent to a condenser, and the condensate was refluxed to the light fraction separation column. The bottom liquid of the light fraction separation column was fed to the ethylene oxide fractionator. Ethylene oxide vapor near the top of the ethylene oxide rectification column was condensed in a condenser, a part of which was refluxed to the ethylene oxide rectification column, and the remainder was extracted as ethylene oxide.
[0082] The extracted ethylene oxide was added to the bottom liquid of the ethylene oxide dehydration tower and fed to a hydration reactor. The reaction was carried out at a pressure of 1.8 MPa (gauge) and a reaction temperature of 150° C. to obtain a 15.2% by mass ethylene glycol aqueous solution. The aqueous ethylene glycol solution was fed to a first evaporator operated at a top pressure of 0.41 MPa gage and a bottom temperature of 153°C. The bottom liquid of the first evaporator was fed to a second evaporator operated at a top pressure of 0.17 MPa gage and a bottom temperature of 136°C. The bottom liquid of the second evaporator was fed to a third evaporator operated at a top pressure of 0.07 MPa gage and a bottom temperature of 124°C. The bottom liquid of the third evaporator was fed to a fourth evaporator operated at a top pressure of -0.03 MPa gage and a bottom temperature of 105°C. The bottom liquid of the fourth evaporator was fed to an ethylene glycol dehydration column, where water was removed, and then fed to an ethylene glycol distillation column. Ethylene glycol was separated from the top of the ethylene glycol distillation column.
[0083] 62 parts by mass of ethylene glycol derived from carbon monoxide gas thus obtained and 83 parts by mass of terephthalic acid derived from fossil fuel were fed as a slurry to a reaction vessel, and an esterification reaction was carried out at 240°C for 5 hours by a conventional direct polymerization method. Then, 0.013 parts by mass of trimethyl phosphate (manufactured by Aldrich) was added (15 mmol% relative to the acid component), and then the polymerization reaction was transferred to a high-temperature vacuum condition. First, the degree of vacuum was raised to 4000 Pa and the polymerization temperature to 280°C in 40 minutes, and then the degree of vacuum was lowered to 200 Pa while keeping the polymerization temperature at 280°C, and a melt polymerization reaction was carried out for 3 hours to synthesize a polyester. The synthesized polyester was discharged in the form of a strand into running water and pelletized by a pelletizer. The pellets were dried at 160°C for 5 hours, and then solid-phase polymerized at 205°C under a nitrogen atmosphere and a vacuum of 50 Pa. When the melt viscosity reached a value equivalent to an intrinsic viscosity of 0.65, the pellets were discharged to obtain the polyester pellets of Example 1.
[0084] The polyester pellets of Example 1 were dried, fed to an extruder, melted at 290°C, and spun from a die with 192 holes. The spun yarn was passed through a 300 mm long heating cylinder at an ambient temperature of 350°C, cooled by blowing cooling air at a temperature of 25°C from the lateral direction, and a spinning oil was applied using an oiling roller. The amount of spinning oil applied was set so that the oil pickup after drawing was 0.5%. The yarn was taken up by a take-up roller at a speed of 660 m / min to obtain an undrawn fiber.
[0085] The obtained undrawn fiber was continuously preheated to 100°C with a preheating roller without being wound once, and was drawn 3.5 times between the preheating roller and the drawing roller. Then, the surface temperature of the drawing roller was adjusted to 140°C, the fiber was preheated to be further easily drawn, and the fiber was drawn 1.43 times between the drawing roller and the heating roller. The surface temperature of the heating roller was set to 257°C. The drawn fiber was subjected to a relaxation heat treatment between the heating roller and the relaxation roller at a relaxation rate of 11%, and was wound up by a winding machine at a speed of 3300 m / min. In this way, the fiber of Example 1 was obtained.
[0086] The fibers of Example 1 were used for the warp and weft, and the warp threads along the longitudinal direction and the weft threads along the width direction were alternately crossed and plain woven on a loom to form a 30 cm x 30 cm gauze. In this way, the gauze of Example 1 was obtained.
[0087] [Comparative Example 1] Polyester pellets of Comparative Example 1, fibers of Comparative Example 1, and gauze of Comparative Example 1 were obtained in the same manner as in Example 1, except that ethylene glycol derived from fossil fuels was used instead of ethylene glycol derived from carbon monoxide gas.
[0088] [Measurement of intrinsic viscosity] The melt viscosity of each of the polyester pellets of Example 1 and Comparative Example 1 was measured at 35° C. using a phenol / tetrachloroethane (component ratio: 3 / 2) solvent, and the intrinsic viscosity was calculated from the melt viscosity. The results are shown in Table 1.
[0089] [Differential Scanning Calorimetry (DSC)] For each of the polyester pellets of Example 1 and Comparative Example 1, measurements were carried out in a nitrogen gas atmosphere using a differential scanning calorimeter (manufactured by Hitachi High-Tech Science Corporation, product name: DSC7000X) in accordance with JIS K7122:2012 (Method for measuring heat of transition of plastics). The measurement sample was 15 mg of polyester pellets cut into pieces with a razor. At this time, the measurement sample was held at 0°C for 5 minutes, then heated from 0°C to 300°C at a heating rate of 10°C / min (first heating), held at 300°C for 1 minute, then cooled from 300°C to 0°C at a cooling rate of 10°C / min (first cooling), and held at 0°C for 5 minutes. Then, the temperature was raised again from 0°C to 300°C at a heating rate of 10°C / min (second heating), and held at 300°C for 1 minute, then lowered from 300°C to 0°C at a cooling rate of 10°C / min (second cooling), and held at 0°C for 5 minutes. Then, the temperature was raised from 0°C to 25°C at a heating rate of 10°C / min. This resulted in DSC curves at the second heating and second cooling. In the DSC curve, the heat of fusion and the heat of solidification were calculated from the area surrounded by the baseline (the line formed by connecting the start point and the end point of the ridgeline from the base to the base) and the peak. The flow rate of nitrogen gas was 20mL / min. The results are shown in Table 1.
[0090] [Measurement of Kjeldahl nitrogen content] The content of Kjeldahl nitrogen contained in the polyester pellets of each of Example 1 and Comparative Example 1 was measured in accordance with JIS K0102:2019 44.1 (Kjeldahl method) and 44.2 (Indophenol blue absorptiometry). The results are shown in Table 1.
[0091] [Measurement of hydrogen molecule content] Each of the polyester pellets of Example 1 and Comparative Example 1 was cut to obtain a test piece of 35 mg. The test piece was subjected to thermal desorption gas-mass spectrometry (TDS-MS) under the following measurement conditions to measure the content of hydrogen molecules contained in the polyester pellets. The results are shown in Table 1. (Measurement conditions) ·Device name: Denshi Kagaku EMD-WA1000S / W type Heating the specimen on the SiC stage Ionization method: Electron Ionization (EI) Measurement mode: SCAN mode Mass range (m / z): 1 to 200 ·Heating conditions: 50℃~100℃ Heating rate: 10℃ / min Holding temperature and holding time: 100℃ for 30 minutes
[0092] [Table 1]
[0093] As is clear from Table 1 above, polyester pellets having carbon monoxide-derived ethylene glycol as a diol unit have larger heats of fusion and solidification in DSC than polyester pellets having fossil fuel-derived ethylene glycol as a diol unit. Furthermore, as is clear from Table 1 above, the polyester pellets having carbon monoxide-derived ethylene glycol as a diol unit have a lower Kjeldahl nitrogen content and hydrogen molecule content than the polyester pellets having fossil fuel-derived ethylene glycol as a diol unit.
Claims
1. A fiber using polyester pellets, the polyester pellets contain a polyester composed of diol units and dicarboxylic acid units, The diol unit contains ethylene glycol produced from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide, The intrinsic viscosity of the polyester pellets is 0.50 dL / g or more and 0.90 dL / g or less.
2. The fiber according to claim 1 , wherein the dicarboxylic acid unit comprises at least one selected from the group consisting of terephthalic acid derived from a fossil fuel, terephthalic acid derived from biomass, and terephthalic acid derived from carbon dioxide gas.
3. The fiber according to claim 1 or 2, wherein the polyester pellets have a heat of fusion of 8 J / g or more during a second heating step as measured by differential scanning calorimetry (DSC) in accordance with JIS K7122:2012.
4. The fiber according to claim 1 or 2, wherein the polyester pellets have a heat of solidification of 7 J / g or more during a second cooling step as measured by differential scanning calorimetry (DSC) in accordance with JIS K7122:2012.
5. 3. The fiber according to claim 1 or 2, wherein the polyester pellets have a Kjeldahl nitrogen content of 90 μg / g or less.
6. The content of hydrogen molecules in the polyester pellets is 7.5×10 17 The fiber according to claim 1 or 2, wherein the number of particles per gram is not more than 1.
7. A textile product using the fiber according to claim 1 or 2.
Citation Information
Patent Citations
Microbial alcohol production process
JP2011512869A
Bio-based polyethylene terephthalate polymer and method for producing the same
JP2011527348A
Bio-based polyethylene terephthalate packaging and method for manufacturing the same
JP2012519748A
Electrolytic cell of carbon dioxide and electrolytic apparatus
JP2018123390A